Early-to-mid Holocene environmental change in the Kallang River Basin, Singapore - Yan, Yu Ting (Nanyang Technological University, 2023)
Climate change and projected sea-level rise are expected to increase risks of coastal inundation and extreme weather events, leading to far-reaching serious socio-economic impacts. The early-to-mid Holocene is the most recent period where rapid sea-level rise occurred simultaneously with warming temperatures. Therefore, understanding the past interplay between rising temperatures, sea-level variability and environmental change during this period provides potential analogues and useful information to facilitate future projections and policies. To this end, this study presents sedimentological, micropaleontological and geochemical analyses conducted on a sediment core (GRBH03) from the Kallang River Basin, Singapore, to investigate environmental change from about 9.1 to 5.8 cal ka BP. The chronology of GRBH03 is constrained by 18 radiocarbon dates, of which 10 are used to construct an age-depth model using the Bchron software. Three sedimentary units were identified from computed tomography scanning (Chapter 3), grain size distribution, Loss on Ignition and X-ray fluorescence core scanning (Chapter 4). Environmental interpretations were aided by the foraminiferal assemblages present, which were dominated by shallow benthic species. The foraminiferal assemblages revealed a shift to shallow marine conditions between 8.9 to 6.4 cal ka BP in response to rapid sea-level rise, followed by a transition to an estuarine brackish environment as the rate of sea-level rise slowed (Chapter 5). 13C and 18O records of three foraminifera species (Ammonia sp., Elphidium sp., and Asterorotalia pulchella) provided insights into the hydroclimate during this period (Chapter 6). Positive excursion of the A. pulchella 13C and 18O values from 8.3 to 8.1 cal ka BP suggest a drying interval, likely associated with the 8.2 ka event.